2022
DOI: 10.1101/2022.09.25.22280229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of temperature and precipitation on the effectiveness of water, sanitation, and handwashing interventions against childhood diarrheal disease in rural Bangladesh: a re-analysis of a randomized control trial

Abstract: Background: Climate change may influence the effectiveness of environmental interventions. We investigated if climate and environment modified the effect of low-cost, point-of-use water, sanitation, and handwashing (WASH) interventions on diarrhea and predicted intervention effectiveness under climate change scenarios. Methods: We analyzed data from a cluster-randomized trial in rural Bangladesh that measured diarrhea prevalence in children 0-2 years from 2012-2016. We matched remote sensing data on temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…This is consistent with the finding of the study that shows that when mean temperature and rainfall increase, households using unimproved sanitation or unimproved water have more cases of diarrhea [43]. On the other hand, the interventional study reported that when there were co-occurrence shifts in temperature and precipitation, the prevalence of childhood diarrhea increased by half in areas with unimproved WASH [72].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the finding of the study that shows that when mean temperature and rainfall increase, households using unimproved sanitation or unimproved water have more cases of diarrhea [43]. On the other hand, the interventional study reported that when there were co-occurrence shifts in temperature and precipitation, the prevalence of childhood diarrhea increased by half in areas with unimproved WASH [72].…”
Section: Discussionsupporting
confidence: 90%
“…We restricted diarrhea analyses to the control arms of the original trial (N=7,320 measurements) because a companion analysis found that intervention effects on diarrhea were modified by climate and environment. 24 For pathogen carriage outcomes, we pooled across all study arms in which specimens were collected (N=1,408 measurements) and included study arm as a covariate.…”
Section: Discussionmentioning
confidence: 99%